Assessment of compliance to the COTPA 2003 legislation in tertiary healthcare institutes of Shimla: a smoke free city in India - Thakur, Anita; Chaudhary, Ankit; Chauhan, Tripti; Gupta, Anmol; Mahajan, Anjali; Barwal, Vijay; Chamotra, Shaina; Chauhan, Nidhi (International Journal Of Community Medicine And Public Health, 2019)
Background: Tobacco smoking is a pandemic affecting populations and contributing to global morbidity and mortality. It is well known that the second hand smoke is equally hazardous like first hand smoke. Cigarette and other tobacco products act 2003 is an effort put forth by Government of India in order to curb this menace and protect people from ill effects of second hand smoke. Methods: The present study was conducted to assess the compliance to smoke free act in tertiary healthcare institutes in Shimla city, Himachal Pradesh. A total of 57 public places and 8 shops in five Tertiary healthcare institutes were evaluated for various provisions of the act. Compliance to different sections of the act was assessed using a structured observational checklist. Results: Signage indicating ban on smoking was seen at 71.9% places. Active smoking was absent at 77.2% places. About 25% shops around the institutes were found selling tobacco products. Signage displaying ban on sale within 100 m of educational institution and sale to minors was not observed at any shop. Tobacco product vendor was seen around 80% of educational buildings. Tobacco free institution signage was seen at 60% of educational premises. Conclusions: The study highlights that the level of compliance did not meet the standards laid down for a smoke free city. Timely and periodic assessment of the compliance must be conducted by the administrative authorities of the institutes for ensuring the adherence and strict implementation of the provisions of the act.